Bratman on identity over time and identification at a time. (2nd January 2017) - Franklin, Christopher Evan
Abstract : According to reductionists about agency, an agent's bringing something about is reducible to states and events (such as desires and beliefs) involving the agent bringing something about. Many have worried that reductionism cannot accommodate robust forms of agency, such as self-determination. One common reductionist answer to this worry (which I call "identification reductionism") contends that self-determining agents are identified with certain states and events, and so these states and events causing a decision counts as the agent's self -determining the decision. In this paper, I discuss Michael Bratman's well-known identification reductionist theory and his general strategy of grounding an agent's identification at a time in the agent's identity over time. I develop two constraints that an adequate identification reductionist theory must satisfy, argue that Bratman's theory cannot satisfy both, and show that his general strategy for grounding an agent's identification at a time in the agent's identity over time is without merit.